The relationship between safety management practice and radiation safety awareness among employee in UUM University Health Centre - Ruzaidi, Ramli (2017)
Safety awareness programs have been conducted comprehensively and actively in order to inspire employees’ engagement and commitment towards safety issues even though from time to time it has been reported that the number of incidents and accidents at the manufacturing firms is keep-on increasing. Furthermore in terms of radiation safety awareness, failure to reduce occupational exposure due to inadequate of knowledge, attitude and action towards ionizing radiation may result in cumulative radiation damage not only in Radiology Professionals but also the other citizens as well. The study was conducted in order to determine the relationship between safety management practice and radiation safety awareness in UUM University Health Centre. In addition, the study was done quantitatively by distributing questionnaires to all employees of University Health Centre. The data from 57 respondents were collected and then analyzed by using SPSS Version 24.0. The findings showed that safety management practice has strong correlation with radiation safety awareness. All these results and findings would provide fruitful guidance for scholars and practitioners in identifying “rooms for improvement” especially in radiation safety awareness campaign.